2012
DOI: 10.1021/ed100828x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Viewing Order of Macroscopic and Particulate Visualizations on Students’ Particulate Explanations

Abstract: A prior study showed that students best make predictions about the outcome of opening a valve between two flasks containing a fluid or vacuum when they view both a demonstration video and a particulate animation, but the study showed no influence from the order in which these visualizations were used. The purpose of this current research was to study the effect of the order of visualization on students’ particulate-level explanations. For this study, first-year general chemistry students in a south-central uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Research evaluating the effectiveness of computer animations depicting the behavior of atoms, molecules, and ions has shown that these visualization techniques can improve students' particulate-level explanations of chemical phenomena (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). In his review of the chemical education research involving the use of computer animations, Sanger (14) summarized the evidence for the effectiveness of particulate-level computer animations compared to instruction without particulate drawings and to instruction with static particulate drawings, and found that although computer animations can sometimes introduce new misconceptions, these animations appear to be useful in helping students to develop particulate-level understanding of many chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research evaluating the effectiveness of computer animations depicting the behavior of atoms, molecules, and ions has shown that these visualization techniques can improve students' particulate-level explanations of chemical phenomena (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). In his review of the chemical education research involving the use of computer animations, Sanger (14) summarized the evidence for the effectiveness of particulate-level computer animations compared to instruction without particulate drawings and to instruction with static particulate drawings, and found that although computer animations can sometimes introduce new misconceptions, these animations appear to be useful in helping students to develop particulate-level understanding of many chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In a follow up study, Williamson et al (13) compared students' particulate-level explanations of the three diffusion experiments described by Velázquez-Marcano et al (8). Half of the students in the newer study viewed the videos first and the animations second, while the other half viewed the animations first and the videos second; both sets of students then viewed the animation and video simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical education literature contains numerous studies that demonstrate the importance of providing students with some type of molecular model when they are carrying out tasks that require the use of spatial reasoning skills (Barak, 2013;Booth et al, 2005;Suits & Sanger, 2013;Williamson et al, 2012). Springer demonstrated that organic chemistry students who watched an instructor properly manipulate computer models outperformed their peers who did not witness the manipulation (Springer, 2014).…”
mentioning
confidence: 99%
“…The study was repeated looking for differences in the reason student gave for the phenomena in the three fluid experiments (Williamson et al, 2012). The VA group (n= 207) was compared to the AV group (n=249).…”
Section: Valequezmentioning
confidence: 99%